Limiting fragmentation at LHC energies - Kellers, Benjamin; Wolschin, Georg (Progress of theoretical and experimental physics, 2019)
Abstract: We investigate the validity of the limiting-fragmentation hypothesis in relativistic heavy-ion collisions at energies reached at the Large Hadron Col